2018
DOI: 10.3389/fneur.2018.00433
|View full text |Cite
|
Sign up to set email alerts
|

Postural Instability Induced by Visual Motion Stimuli in Patients With Vestibular Migraine

Abstract: Patients with vestibular migraine are susceptible to motion sickness. This study aimed to determine whether the severity of posture instability is related to the susceptibility to motion sickness. We used a visual motion paradigm with two conditions of the stimulated retinal field and the head posture to quantify postural stability while maintaining a static stance in 18 patients with vestibular migraine and in 13 age-matched healthy subjects. Three parameters of postural stability showed differences between V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 31 publications
4
32
0
1
Order By: Relevance
“…Similar findings were recently demonstrated by Lim et al (2018), in a combined postural and visual motion study. Vertical movement of horizontal lines in the peripheral visual field, but not the central visual field, caused significant motion sickness and imbalance.…”
Section: Visual Stimulation and Motion Sicknesssupporting
confidence: 90%
See 3 more Smart Citations
“…Similar findings were recently demonstrated by Lim et al (2018), in a combined postural and visual motion study. Vertical movement of horizontal lines in the peripheral visual field, but not the central visual field, caused significant motion sickness and imbalance.…”
Section: Visual Stimulation and Motion Sicknesssupporting
confidence: 90%
“…At first inspection, these visually induced cases of motion sickness would appear to invalidate the Bles-Bos hypothesis, or to seriously weaken it. However, as recently demonstrated by Lim et al (2018) in a study of central and peripheral exposure to horizontal lines oscillating vertically, there may be other ways to interpret the Golding et al data. In the Lim et al study, presentation of vertically oscillating horizontal lines did not cause motion sickness when presented in frontal, foveal vision, but it did do so when presented to the visual periphery.…”
Section: Does the Bles-bos Hypothesis Hold For Visually Induced Motiomentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, patients with VM have shown compromised body balance in static posturography tests, and higher visual dependency and low stability of the postural control system when maintaining quiet standing [67,76]. Brain MRI is unremarkable in VM sufferers, although some studies found that grey matter volume of some brain regions of patients with VM is significantly larger than in patients with migraine or healthy controls, mostly areas linked with assessment, integration and pain expectations as well as those associated with mood and anxiety [16,77].…”
Section: Laboratory Findingsmentioning
confidence: 99%